PERBAIKAN DAN PERHITUNGAN BEBAN MAKSIMAL YANG DIIJINKAN PADA GANTRY CRANE - , ALBERTUS NOVAN SUSETIO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
deflection The duty this final obtained inspiration to fix gantry cranes and performing calculations as a means of practicing the science which has been taught in a Diploma Program of Mechanical Engineering of Gadjah Mada University. deflection. There are two stages in making this thesis. The first is to improve crane to fix bad welds, painting, and adding wheels as mobilization. The second calculates the critical load on gantry crane in order to determine the strength of the gantry cranes without deflection The result analysis and discussion writer about analysis on gantry cranes can be concluded that capable of being raised the maximum gantry cranes framework without an deflection 0,57T.